WEBSITE QUALITY ANALYSIS OF PT. ORIGINAL ISOAE SOLUSINE BY USING THE WEBQUAL 4.0 METHOD - Fadly, Raihan Abi; Ryansyah, Muhamad; Taufik, Andi (Universitas Khairun, 2024)
Customer satisfaction is an important benchmark for the company. PT. Asli Isoae Solusine wants to improve the quality of its website exists so that customers are increasingly satisfied, but the company has not carried out an assessmen on customer satisfaction on the company profile page. The purpose of This research is to measure the level of superior quality of the company's website PT Profile Original Isoae Solusine based on user perceptions of this research using the webqual 4.0 method which has 3 main variables Usability (X1), Information Quality (X2) and Service Interaction (X3) to determine the effect quality of use, influence of interaction quality, and influence of information quality on a website. Using questionnaires as a data collection technique, Questionnaires were distributed to PT employee staff. Asli Isoae Solusine via social media. The overall quality of the https://isoae.id website is based on the RÂ² value contributed 58% to user satisfaction. Service interaction makes a significant contribution to user satisfaction of 0.112 based on the output regression coefficients table. Usability and quality information has an influence but is not significant on user satisfaction of 0.044 and 0.011 based on the output regression coefficients table. This is possible occurs when users believe that the usability of the site and the quality of the information are not significant or only occasionally used by visitors.